Community engagement among forest goers in a malaria prophylaxis trial: implementation challenges and implications - Conradis-Jansen, Franca; Tripura, Rupam; Peto, Thomas J.; Callery, James J.; Adhikari, Bipin; Ean, Mom; Jongdeepaisal, Monnaphat; Pell, Christopher; Khonputsa, Panarasri; Murgia, Riccardo; Sovannaroth, Siv; Müller, Olaf; et al. (Malaria journal, 2023)
Malaria transmission in Southeast Asia is increasingly confined to forests, where marginalized groups are exposed primarily through their work. Anti-malarial chemoprophylaxis may help to protect these people. This article examines the effectiveness and practical challenges of engaging forest-goers to participate in a randomized controlled clinical trial of anti-malarial chemoprophylaxis with artemether-lumefantrine (AL) versus a control (multivitamin, MV) for malaria in northeast Cambodia.
Veröffentlicht: 08. Juni 2023
Gesehen am 15.08.2023